The Effect Of Harvest Insentives On The Performance Of Harvester Employees Kanopan Ulu Estate PT. MP Leidong West Indonesia - Lubis, Fadli Akbar; Dibisono, Muhammad Yusuf; Parinduri, Sulthon; Maulana, Imron (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
Premi as harvest incentives for employees on oil palm plantations are an important element in improving employee performance. Management in oil palm plantations is faced with production targets and also the capabilities of employees achieve production targets. In the palm oil plantation industry in Indonesia, the role of harvest employees is very important in the production process. The expertise of a harvester is an added value for the company to obtain maximum production results, both in quantity and quality. It's not just about being able to harvest, but it must be accompanied by techniques and compliance with the Standard Operating Procedure (SOP) in company. This research aims to analyze how the harvest premi system applies at PT. MP Leidong West Indonesia, Sialang Taji Village, South Kualuh District, North Labuhanbatu Regency, North Sumatra Province. This research analyzes how the harvest premi affects employee performance. The types of data used are primary data and secondary data. The data analysis method used in this research is quantitative descriptive using a likert scale, instrument test, regression test, partial test and determinant test. Before carrying out a simple linear regression test, instrument tests such as validity and reliability tests are first carried out by distributing questionnaires to respondents. The results of the research show that there is a positive effect of the variable (X), that is harvest premi, on the variable (Y), that is employee performance. The determinant coefficient test (R2) shows that the harvest premi has an effect on employee performance variables is 72.9%.